Global trends and hotspots in the digital therapeutics of autism spectrum disorders: a bibliometric analysis from 2002 to 2022 - Wu, Xuesen; Deng, Haiyin; Jian, Shiyun; Chen, Huian; Li, Qing; Gong, Ruiyu; Wu, Jingsong (Frontiers in Psychiatry, 2023)
Introduction: Autism spectrum disorder (ASD) is a severe neurodevelopmental disorder that has become a major cause of disability in children. Digital therapeutics (DTx) delivers evidence-based therapeutic interventions to patients that are driven by software to prevent, manage, or treat a medical disorder or disease. This study objectively analyzed the current research status of global DTx in ASD from 2002–2022, aiming to explore the current global research status and trends in the field. Methods: The Web of Science database was searched for articles about DTx in ASD from January 2002 to October 2022. CiteSpace was used to analyze the co-occurrence of keywords in literature, partnerships between authors, institutions, and countries, the sudden occurrence of keywords, clustering of keywords over time, and analysis of references, cited authors, and cited journals. Results: A total of 509 articles were included. The most productive country and institution were the USA and Vanderbilt University. The largest contributing authors were Warren, Zachary and Sarkar, Nilanjan. The most cited journal was the Journal of Autism and Developmental Disorders. The most cited and co-cited articles were Brian Scarselati (Robots for Use in Autism Research, 2012) and Ralph Adolphs (Abnormal processing of social information from faces in autism, 2001). “Artificial Intelligence”, “machine learning”, “Virtual Reality”, and “eye tracking” were common new and cutting-edge trends in research on DTx in ASD. Discussion: The use of DTx in ASD is developing rapidly and gaining the attention of researchers worldwide. The publications in this field have increased year by year, mainly concentrated in the developed countries, especially in USA. Both Vanderbilt University and Yale University are very important institutions in the field. The researcher from Vanderbilt University, Warren and Zachary, his dynamics or achievements in the field is also more worth our attention. The application of new technologies such as virtual reality, machine learning and eye tracking in this field has driven the development of DTx on ASD and is currently a popular research topic. More cross-regional and cross-disciplinary collaborations are recommended to advance the development and availability of DTx.